ANALISIS PENERAPAN MODEL PROBLEM BASED LEARNING(PBL) PADA MATERI EKOSISTEM BIOLOGI - Desi Novianty Br Ginting; Donna Arista Stefani Sinaga; Ruth DamaiYanti Sari Siagian; Stevani Azharia Br Ginting; Yohana L Purba; Widya Arwita; Rizal Mukra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research aimed to examine the impact of PBL on enhancing students' conceptual understanding and critical thinking skills, as well as to identify challenges encountered during implementation. A mixed-methods approach was employed, with quantitative data collected through Likert-scale questionnaires and qualitative data gathered via semi-structured interviews; data analysis was conducted using descriptive and inferential statistics. Findings indicate that the systematic implementation of PBL effectively improved student engagement, analytical abilities, and comprehension of biotic and abiotic relationships within ecosystems. Furthermore, the integration of real-world problems and digital media enhanced student motivation and active participation. However, challenges such as time constraints, limited learning resources, and passive participation among some students were observed. Mitigation strategies including more efficient time management and the provision of additional guidance proved effective in addressing these obstacles. In conclusion, PBL is an effective approach for improving the quality of biology education, particularly in ecosystem-related topics, provided that teachers are adequately prepared and appropriate strategic adjustments are implemented.